Impact of intermittent fasting on the lipid profile: Assessment associated with diet and weight loss. (April 2018) - Santos, Heitor O.; Macedo, Rodrigo C.O.
Abstract: Intermittent fasting, whose proposed benefits include the improvement of lipid profile and the body weight loss, has gained considerable scientific and popular repercussion. This review aimed to consolidate studies that analyzed the lipid profile in humans before and after intermittent fasting period through a detailed review; and to propose the physiological mechanism, considering the diet and the body weight loss. Normocaloric and hypocaloric intermittent fasting may be a dietary method to aid in the improvement of the lipid profile in healthy, obese and dyslipidemic men and women by reducing total cholesterol, LDL, triglycerides and increasing HDL levels. However, the majority of studies that analyze the intermittent fasting impacts on the lipid profile and body weight loss are observational based on Ramadan fasting, which lacks large sample and detailed information about diet. Randomized clinical trials with a larger sample size are needed to evaluate the IF effects mainly in patients with dyslipidemia. Graphical abstract: Highlights: IF may be a method to aid in the improvement of the lipid profile in healthy, obese and dyslipidemic men and women. The reduction of total cholesterol, LDL, triglycerides and increase HDL levels improves through IF. The majority of studies that analyzed the impact of IF on the lipid profile are carried out in Ramada period.